Tribology for energy conservation proceedings of the 24th Leeds-Lyon Symposium on Tribology, held in the Imperial College of Science, Technology, and Medicine, London, UK, 4th-6th September 1997 - Dowson, D. (Tribology series)
The 24th Leeds-Lyon Symposium was held in London from 4th-6th September 1997, where it was hosted by the Imperial College of Science, Technology and Medicine. The meeting addressed the topic of "Tribology for Energy Conservation" and attracted a wide range of stimulating papers and speakers. Some 150 delegates from nineteen countries attended and about sixty papers were presented in fifteen sessions. These covered the topics of lubricants, wear, friction reduction, hydrodynamics, elastohydrodynamic lubrication, surface roughness, manufacturing, component life (including condition mon.